CONTRIBUTION OF THE DEVELOPMENT OF CACAO BEANS TO ELEVATING EMPLOYMENT, WELFARE OF SOCIETY AND FOOD SECURITY IN SOPPENG, WEST SULAWESI - Zainal Abidin Sahabuddin (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
The selection of seeds is the first step to get focused to increase cacao production. Providing seeds with quality is vital from not only the quantity but also the ability to produce. This research wants to analyze the government contribution to the potential Cacao seeds in Soppeng in order to enlarge the working opportunity, increase the people's welfare, and ensuring food security, as well as to identify the impending factors. To achieve these intentions, furthermore, qualitative research procedures stand applied. The data get collected through observations, interviews, and documentation. Based on the analysis, this study finds that the budget of the local government for providing seeds cannot cover society's demands. Moreover, the impending factors are the financial limitations of farmers and pests and vascular streak dieback.